Assessing The Effectiveness Of Joint Interventions By Social Services, Nursing, And Pharmacy In Enhancing Treatment Adherence (The Review of Diabetic Studies, 2025)
Background: Treatment adherence is a recurring problem in healthcare delivery, and rates of non-adherence of 20-50% have been found in various chronic diseases. Multidisciplinary interventions such as social services, nursing, and pharmacy interventions have been demonstrated to overcome multiple barriers to adherence effectively.Objective:  the effectiveness of multidisciplinary collaborative interventions by social services, nursing, and pharmacy in enhancing treatment adherence in chronic patients.Methods: Prospective 12-month questionnaire survey was performed among 450 chronic disease patients. Patients were randomly divided into intervention (n=225) and control (n=225) groups. Intervention group underwent coordinated pharmacy care, nursing, and social services. Morisky Medication Adherence Scale-8 (MMAS-8) and self-reported questionnaires were used to assess treatment adherence at baseline, 6 months, and 12 months.Results: There was better adherence score in the intervention group (5.2 ± 1.8) at baseline to 12 months (7.1 ± 1.2) than in controls (5.3 ± 1.7 to 5.8 ± 1.9; p